Improving The Heat Value of Biobriquettes Made From Rice Husk and Cabbage with The Addition of Palm Oil - Yanatra Budi Pramana; Dwi Ana A; Nanik AR (Tibuana, 2022)
Biobriquette can be used as an alternative fuel because it is made from inexpensive materials and uses simple technology, and it is expected to help overcome the energy (fossil) crisis. The problem is determining how to boost the calorific value of briquettes made from waste biomass materials. Cabbage contains approximately 18.80% fiber, so there is cellulose content that can be processed into high-value products such as briquettes, and using rice husks as fuel can increase the calorific value. The goal of this study is to determine the best calorific value of biobriquettes by varying the method of adding coconut oil and the composition of rice husks and cabbage. The stages of making cabbage and rice husk biobriquettes are raw material preparation, carbonization, adhesive manufacture, briquetting, and quality testing. The variables used are variations in the composition of rice husks: cabbage in ratios of 40:60, 50:50, 60:40, 70:30, and 80:20, as well as the variable method of giving palm oil by mixing with ingredients and dyeing after it becomes briquettes. According to the findings of this study, the best biobriquette mixing ratio resulted in the highest calorific value found in a mixture of 40% rice husk and 60% cabbage with the method of adding palm oil by dipping, with a calorific value of 6.283 kcal/g, a combustion rate of 0.0616 g/minute, and the duration of the flame is 60.26 minutes.